Synthesis And Characterization Of Gold Nanoparticles Using Beluntas Leaf Extract Plucheaindica - Dewi Lidiawati; Abdul Wahid Wahab; Abdul Karim (Hasanuddin University, 2019)
Gold nanoparticles have been successfully synthesized using beluntas leaf extract as reducing agents. This is indicated by the change of the color from yellow gold to purple solution after the addition of the beluntas leaf extract. The gold nanoparticles formed were observed for 92 hours using uv-vis and obtained stability after 72 hours with a wavelength about 545.50-546.00 nm. The size distribution of gold nanoparticles was determined using Particle Size Analyzer (PSA) with an average distribution of 101.6 nm. Based on the characterization using XRD, the diffraction pattern obtained at 2θ is 38.1077; 44,2935; 64,5155; 77,4862 which show the presence of gold nanoparticles. Furthermore, it was characterized using SEM EDX showed that the average shape of gold nanoparticles was spherical with a composition ofAu 48%, C 43.33%, and several other elements around 8.67%.